Anteseden dan Konsekuensi Work life balance pada Pegawai Wanita Institut Teknologi Kalimantan - Errina Ekaastuti, Rismawanti; Althalets, Fareis (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the effect of work family conflict, emotional intelligence and work life balance on the performance of female employees at the Kalimantan Institute of Technology. This research employed an associative research design with a quantitative approach. The population of this study consisted of female educational staff at the Kalimantan Institute of Technology. The sampling technique used was nonprobability sampling with a saturated sample. The sample of this study consisted of 53 female educational staff at the Kalimantan Institute of Technology. Data collection was conducted using questionnaires distributed both in person and online. The data analysis technique used was path analysis with SmartPLS 4.1.1.6 software. The results of this study indicate that work family conflict does not have a significantly effect on performance, emotional intelligence and work life balance significantly affect performance, work family conflict and emotional intelligence significantly affect work life balance.